2014
DOI: 10.1007/s10493-014-9855-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of Drosophila doublesex, transformer-2, intersex, fruitless-like, and vitellogenin homologs in the parahaploid predator Metaseiulus occidentalis (Chelicerata: Acari: Phytoseiidae)

Abstract: Characterization and expression analyses are essential to gain insight into sex-determination pathways in members of the Acari. Little is known about sex determination at the molecular level in the western orchard predatory mite Metaseiulus occidentalis (Arthropoda: Chelicerata: Arachnida: Acari: Phytoseiidae), a parahaploid species. In this study, eight genes previously identified as putative homologs to genes involved in the sex-determination pathway in Drosophila melanogaster were evaluated for sex-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…The dsx clade contained sequences from several basal insect orders, crustaceans, and chelicerates (Supplemental Figure 1), and included experimentally characterized dsx genes from the branchiopod crustacean D. magna (NCBI accession number BAJ78307.1), the decapod crustacean F. chinensis (AUT13216.1), and the mite M. occidentalis (XP003740429.2 and XP003740430.1). In these species, the dsx genes are not spliced sex-specifically, but are transcribed in a strongly male-biased fashion (53,54,57). dsx genes from holometabolous insects, which direct male and female differentiation via alternative spliceforms, are also present in this clade.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dsx clade contained sequences from several basal insect orders, crustaceans, and chelicerates (Supplemental Figure 1), and included experimentally characterized dsx genes from the branchiopod crustacean D. magna (NCBI accession number BAJ78307.1), the decapod crustacean F. chinensis (AUT13216.1), and the mite M. occidentalis (XP003740429.2 and XP003740430.1). In these species, the dsx genes are not spliced sex-specifically, but are transcribed in a strongly male-biased fashion (53,54,57). dsx genes from holometabolous insects, which direct male and female differentiation via alternative spliceforms, are also present in this clade.…”
Section: Resultsmentioning
confidence: 99%
“…We propose that the canonical insect mechanism of sexual differentiation based on sex-specific splicing of dsx and tra evolved gradually in hemimetabolous insects, and may not have been fully assembled until the last common ancestor of the Holometabola (Figure 8). In crustaceans, mites, and non-arthropod animals, dsx and its homologs act as male-determining genes that are transcribed in a male-specific fashion and are dispensable for female sexual differentiation (53,54,57). One of the earliest events in insects was the evolution of sex-specific dsx splicing, where dsx is transcribed in both sexes but produces alternative isoforms in males vs females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sciara spp., in contrast, dsx mRNAs are not sex‐specific, but the relative abundances of dsx transcripts are sex‐specific (Ruiz et al ., ). In the crustacean D. magna and the arachnid M. occidentalis , dsx pre‐mRNA regulates sexual dimorphism via sex‐biased expression in males (Kato et al ., ; Pomerantz et al ., ; Pomerantz & Hoy, ). The current study demonstrated that, like Sciara spp., B. tabaci lacks a sex‐specific dsx transcript and that the expression level of Btdsx , like the expression levels of dsx in D. magna and M. occidentalis , was significantly higher in males than females.…”
Section: Discussionmentioning
confidence: 99%
“…In most insects and as indicated earlier, male‐ and female‐specific sexual development occurs via the sex‐specific splicing of dsx pre‐mRNA (Baker & Wolfner, ; Scali et al ., ; Cho et al ., ; Shukla & Palli, ). In the crustacean Daphnia magna and the arachnid Metaseiulus occidentalis , however, dsx pre‐mRNA regulates sexual dimorphism via sex‐biased expression in males (Kato et al ., ; Pomerantz et al ., ; Pomerantz & Hoy, ).…”
Section: Introductionmentioning
confidence: 97%